Reclaiming the relationship with bodily knowing through movement in nature - Edwards, Lorna; Breden, Andreas; Santin, Chiara; Van Lawick, Justine; van der Elst, Erik (Murmurations: Journal of Transformative Systemic Practice, 2022)
I hosted a workshop on the subject of reclaiming the relationship with bodily knowing through movement in nature at Brathay Hall, Ambleside in May 2022. The idea was to create a space for therapists to explore and deconstruct binaries that connect and separate us and nature. While we are nature, I am referring to the human/nature binary created by us humans.